Characterization of novel peptide-specific antibodies against the translation elongation factor eEF1A2 and their application for cancer research - Shalak, V.F.; Vislovukh, A.A.; Novosylna, O.V.; Khoruzhenko, A.I.; Kovalenko, M.I.; Kolesanova, E.F.; Egorova, E.A.; Mishin, A.A.; Krotevych, M.S.; Skoroda, L.V.; Negrutskii, B.S. (Вiopolymers and Cell, 2014)
Aim. We intend to characterize the new peptide-specific antibodies against the isoform 2 of translation elongation factor 1A (eEF1A2) and determine its presence in the postoperative samples of human breast, lung and stomach tumor tissues. Methods. The analysis of antibody specificity was performed by enzyme-linked immunosorbent assay, immunoblotting and immunohistochemistry. Immunoblotting and immunohistochemistry were used for the determination of the eEF1A2 in the human tumor samples, as well as in the samples of normal tissues surrounding tumors. Results. The antibodies obtained against the eEF1A2 specifically recognized this protein in the cell extracts and histological sections and did not cross-react with the elongation factor 1A isoform 1. eEF1A2 was revealed in the postoperative samples of breast, lung and stomach tumors as well as in the putative normal tissues surrounding tumors. Conclusions. The antibodies obtained against eEF1A2 are highly specific for the antigen and can be used for the immunological studies of tumors. Мета. Охарактеризувати особливості нових пептидоспецифічних антитіл проти другої ізоформи фактора елонгації трансляції 1А (eEF1A2). Визначити присутність цієї ізоформи у післяопераційних зразках пухлин молочної залози, легенів, шлунку людини і порівняти із зразками умовної норми відповідних тканин. Методи. Специфічність антитіл аналізували методами імуноферментного аналізу, імуноблотингу та імуногістохімії. Iмуноблотинг та iмуногiстохімію використано для визначення eEF1A2 в зразках пухлин людини, а також умовної норми. Результати. Встановлено, що отримані антитіла проти eEF1A2 специфічно розпізнають зазначений білок в екстрактах та на гістологічних зрізах і не виявляють перехресної взаємодії з першою ізоформою фактора елонгації. Визначено, що фактор eEF1A2 присутній в післяопераційних зразках пухлин молочної залози, легенів і шлунку, а також в умовно нормальних зразках цих тканин. Висновки. Нами одержано високоспецифічні антитіла проти eEF1A2, які можна використовувати в імунологічних дослідженнях зразків пухлин. Цель. Охарактеризовать особенности новых пептидоспецифических антител против второй изоформы фактора элонгации трансляции 1А (eEF1A2). Определить наличие этой изоформы в послеоперационных образцах опухолей молочной железы, легких, желудка человека и сравнить с условной нормой соответствующих тканей. Методы. Специфичность антител анализировали методами иммуноферментного анализа, иммуноблотинга и иммуногистохимии. Методы иммуноблоттинга и иммуногистохимии использовали для определения eEF1A2 в образцах опухолей человека, а также условной нормы. Результаты. Установлено, что полученные антитела против eEF1A2 специфически распознают этот белок в экстрактах и на гистологических срезах и не выявляют перекрестного взаимодействия с первой изоформой фактора элонгации. Мы определили, что фактор eEF1A2 присутствует в послеоперационных образцах молочной железы, легких и желудка, а также в условно нормальных образцах этих тканей. Выводы. Полученные нами антитела против eEF1A2 являются высокоспецифическими по отношению к антигену и могут быть использованы в иммунологических исследованиях опухолей.